Multigroup Analysis Keberterimaan Dosen dan Keberlanjutan Penerapan Aplikasi Pembelajaran Daring pada Perguruan Tinggi di Jakarta - Widiarto, Setyo; Darmadi, Roby (Program Studi Teknik Informatika Universitas Pamulang, 2024)
As information technology develops and facilitates Internet access, universities are required to be able to optimize the use of online learning applications to support the teaching and learning process. The implementation of online learning applications after the COVID-19 pandemic for teachers still has some problems, such as preparing good learning content, the reliability of the supporting infrastructure, and the faculty's ability to understand all the features of online teaching.. This research aims to determine lecturers' acceptance of learning that utilizes online applications and its sustainability in the future. 100 respondents' data obtained from 27 universities in the DKI Jakarta area was tested using structural equation modeling (SEM) with multigroup analysis, resulting in the research conclusion that ease of use and access to e-learning are the dominant factors influencing lecturers' acceptance of online learning applications, which at the next stage will determine the sustainability of the use of information technology in the learning process in higher education. The actual condition variable for using the system influences the intention to reuse, while the other variables: perceived usefulness, ease of use, and attitude do not influence the intention to reuse. MGA analysis resulted in no difference in the influence between the male and the female group on the relationship between the variables studied.